Service gaps in the general banking department of Mercantile Bank Limited, Mohakhali Branch - Khan, Asif Ali (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.